Measurement of Radioactive Caesium Isotopes by Accelerator Mass Spectrometry - MacDonald, Cole (Université d'Ottawa / University of Ottawa, 2014)
The first measurements of the radioactive 135Cs and 134Cs isotopes were made on an accelerator mass spectrometer. The natural Ba interference was suppressed using an isobar separator for anions (ISA) in order to measure the less abundant isobaric 134Cs and 135Cs isotopes. It was found that the Ba interference could be suppressed by a factor of 2 × 10^5 while 25% of Cs was transmitted. Furthermore, through comparing the known natural abundance of Ba isotopes to the measured concentration in a sample it was shown that the ISA does not introduce significant mass dependant fractionation at the level of 0.8%. A slow sequential injection analysis technique was developed to measure 135Cs using 134Cs as a reference isotope. This technique also permitted the monitoring of Ba interference. The ionization efficiency of Cs when analyzed in the molecular anion form, CsF2^- , was on the order of 10^−7 while the total measurement efficiency was 1.7×10^−9. The abundance sensitivity of this system was found to be 135Cs/ 133Cs = (1.3 ± 1.7) × 10^−10 , corresponding to a 3σ detection limit of 132.5 pg of analyte per target. Lastly, using the developed AMS techniques, beta spectroscopy, gamma spectroscopy, and isotope production, a measurement of the half life of 135Cs was made. The two measurements of the half life of 135Cs were 0.72 ± 0.32 Ma and 0.99 ± 0.42 Ma.
Keywords: Accelerator Mass Spectrometry; Isobar Separation